The current situation of the people with mental illness in the traditional healer centers in Sudan - Sorketti, E.A.; Habil, M.H. (Malaysian Psychiatric Association, 2009)
In Sudan traditional healing is the most prevalent method for the treatment of mentally sick people mostly due to lack of economic resources, inaccessibility of medical services, and lack of awareness among the population and the high prices of psychiatric services. Now University of Malaya, the leading research institute in Malaysia, is conducting a research in this area of mental health in Sudan, trying to explore more in this area of mental health and traditional healing.